Chloroquine–Primaquine Therapeutic Efficacy, Safety, and Plasma Levels in Patients with Uncomplicated Plasmodium vivax Malaria in a Colombian Pacific Region (2019)
ABSTRACT: In Colombia, published studies for the treatment of uncomplicated Plasmodium vivax malaria with chloroquine–primaquine (CQ-PQ) are scarce. The aim of the study was to evaluate the therapeutic efficacy and safety profile of this combination. A clinical trial was performed in adults with uncomplicated P. vivax malaria using the 28-day World Health Organization validated protocol. Patients received supervised antimalarial treatment and the primary efficacy end point was the clinical and parasitological response. Safety was assessed through adverse events surveillance, and plasma levels of antimalarial drugs were measured. A total of 77 patients were included. Adequate clinical and parasitological response rate diagnosed by thick blood smear examination was achieved in 72 of 73 patients (98.6%) with a complete 28-day follow-up. There were two parasitological therapeutic failures (TFs) (2.9%) on day 28, established by polymerase chain reaction among 68 patients, one of them with a positive film. No adverse events were detected. After completing the antimalarial treatment, all patients reached adequate plasma concentrations of CQ and desethylchloroquine (DECQ), with medians of 302.9 and 104.0 ng/mL, respectively. Uncomplicated P. vivax malaria treatment with CQ–PQ standard treatment was effective and safe in the study population; TFs were not associated with low plasma levels of CQ and DECQ.